Implementasi Metode Modified K - Nearest Neighbor (MK-NN) Untuk Klasifikasi Cedera Pada Pemain Futsal - Putut Abrianto; Nurul Hidayat; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
One of the sport that is often played by the general public is futsal where is the futsal follows the basics of football, but the difference with football is that futsal is played by a few people and is played on a relatively smaller place or field. In every futsal game, of course there must be a player who suffered an injury. Slippery and uneven field conditions are the factors that affect futsal players that can easily fall and subsequently suffer injuries during futsal games. The existence of a system that can classify the types of injuries suffered by futsal players will greatly help solve this problem. Utilizing the modified k - nearest neighbor method implemented using Java language, a maximum accuracy of 97% is obtained from different K values.